Encyclopedia of Business Aircrafts - Shaw, Zula, author 646438 (Delhi, India : Orange Apple : World Technologies, 2012)
The Embraer Legacy 450 is a business jet being developed by Brazilian aircraft manufacturer Embraer. Launched as a concept called the MLJ (Mid-Light Jet) at the NBAA Convention in 2007, the Legacy 450 (and its big brother the Legacy 500) were officially launched at EBACE in May 2008 It is designed to carry 7 to 8 passengers over 2,300 nautical miles (4,300) The aircraft has full fly - by - wire flight controls , a Collins Proline Fusion flight scheduled for 2012 , and entry into service is in late 2013.